2021
DOI: 10.1152/ajpregu.00234.2020
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of soluble guanylate cyclase diminishes intrauterine growth restriction in a rat model of placental ischemia

Abstract: Placental ischemia in preeclampsia (PE) results in hypertension and intrauterine growth restriction (IUGR). Stimulation of soluble guanylate cyclase (sGC) reduces blood pressure in the clinically relevant reduced uterine perfusion pressure (RUPP) rat model of PE implicating involvement in RUPP-induced hypertension. However, the contribution of sGC in the development of IUGR in PE is not known. Thus, this study demonstrated the efficacy of Riociguat, a sGC stimulator, in IUGR reversion in the RUPP rat model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 73 publications
0
12
1
Order By: Relevance
“…Collectively, these studies suggest that a reduction in NO bioavailability may contribute to endothelial dysfunction and the generation of oxidative stress in response to placental ischemia in the RUPP model of PE. Our laboratory previously reported that urinary, placental, and uterine artery cGMP are decreased in the RUPP model of placental ischemia in association with a reduction in fetal weight at gestation day 20 (G20) (19). We also showed that targeting the sGC pathway with a sGC stimulator, Riociguat, during late gestation restores the decrease in cGMP in association with improved uterine blood flow and placental morphology and attenuation of reduced fetal weight at G20 in the RUPP (19).…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Collectively, these studies suggest that a reduction in NO bioavailability may contribute to endothelial dysfunction and the generation of oxidative stress in response to placental ischemia in the RUPP model of PE. Our laboratory previously reported that urinary, placental, and uterine artery cGMP are decreased in the RUPP model of placental ischemia in association with a reduction in fetal weight at gestation day 20 (G20) (19). We also showed that targeting the sGC pathway with a sGC stimulator, Riociguat, during late gestation restores the decrease in cGMP in association with improved uterine blood flow and placental morphology and attenuation of reduced fetal weight at G20 in the RUPP (19).…”
Section: Introductionmentioning
confidence: 81%
“…All animals undergoing surgical procedures were anesthetized using 2-5% isoflurane by inhalation. The Sham or RUPP procedure was performed at gestational day 14 (G14) with analgesics (Rodent MD's, Rimadyln, 2 mg/tablet, Bio-Serve, Flemington, NJ) provided before and for 3 days postsurgery (19). Completion of parturition was recorded on an hourly basis starting at day 21 of gestation (G21).…”
Section: Animals and Experimental Detailsmentioning
confidence: 99%
See 3 more Smart Citations